Removal of 2-naphthalenesulfonic acid using novel dual functional weakly basic anion exchange resins from aqueous solution - Yue Sun; Weisheng Zheng; Deqiang Yin (Adsorption Science & Technology)
Two novel weakly basic anion exchange resins BNH and BN2 bearing two different functional groups was fabricated via the two-step amination of chloromethylated polystyrene-divinylbenzene beads with dibutylamine and dimethylamine. The adsorption properties of BNH and BN2 for the 2-naphthalenesulfonic acid (NSA) removal from wastewater were compared with two synthesized monofunctional anion exchange resins BN0 and BN6 (derived from dimethylamine and dibutylamine, respectively). The experimental data revealed that the adsorption process on the four resins fitted well with the pseudo-second-order kinetics equation and the equilibrium isotherms were in good agreement with the Langmuir model. Thermodynamic analyses illustrated that 2-naphthalenesulfonic acid adsorption onto resins was an endothermic and spontaneous process. Importantly, BN2 still displayed relatively high adsorption capacity in the existence of Na 2 SO 4 , indicative of an excellent selectivity for 2-naphthalenesulfonic acid over sulfate than other resins. The obtained results elucidate that BN2 could have potential industrial application in effluent disposal fields because of its superior selectivity, acceptable kinetics, and desorption capability.